2021
DOI: 10.5272/jimab.2021271.3634
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Hyperuricemia as a Potential Metabolic Risk Factor for Coronary Artery Calcification in Patients With Atrial Fibrillation or Heart Failure

Abstract: Purpose: To assess the role of asymptomatic hyperuricemia for the presence and severity of coronary arterial calcium (CAC) in adults with different cardiovascular (CV) pathology and its association with conventional CV risk factors. Material/Methods: Adults (n=81) of both genders were divided into controls: with moderate- to high risk without known CVD; AF-group: CVD-patients with paroxysmal or persistent atrial fibrillation in sinus rhythm, HF–group: heart failure subjects with preserved ejection fraction. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…There are studies connecting UA levels with oxidative stress [3] and inflammation [4] . Many studies have demonstrated that elevated UA level in humans is an independent risk factor for hypertension [5] , diabetes [6] , cardiovascular disease [7] , endothelial dysfunction [8] , coronary artery calcification [9] , vascular damage [10] , obesity and metabolic syndrome. [11,12] Some reports reveal that physiological concentrations of uric acid could induce gene expression of macrophage-secreted inflammatory cytokines, such as monocyte chemoattractant protein-1 (MCP-1), and growth factors, such as platelet-derived growth factor.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies connecting UA levels with oxidative stress [3] and inflammation [4] . Many studies have demonstrated that elevated UA level in humans is an independent risk factor for hypertension [5] , diabetes [6] , cardiovascular disease [7] , endothelial dysfunction [8] , coronary artery calcification [9] , vascular damage [10] , obesity and metabolic syndrome. [11,12] Some reports reveal that physiological concentrations of uric acid could induce gene expression of macrophage-secreted inflammatory cytokines, such as monocyte chemoattractant protein-1 (MCP-1), and growth factors, such as platelet-derived growth factor.…”
Section: Introductionmentioning
confidence: 99%